2003
DOI: 10.1107/s0108270103024673
|View full text |Cite
|
Sign up to set email alerts
|

Bis(2,5-dimethoxy-4-methylphenyl)methane and bis(2,5-dimethoxy-3,4,6-trimethylphenyl)methane

Abstract: Bis(2,5-dimethoxy-4-methylphenyl)methane, C(19)H(24)O(4), (IIa), was obtained and characterized as a minor product from the reaction of toluhydroquinone dimethyl ether (1,4-dimethoxy-2-methylbenzene) with N-(hydroxymethyl)trifluoroacetamide. Similarly, bis(2,5-dimethoxy-3,4,6-trimethylphenyl)methane, C(23)H(32)O(4), (IIb), was prepared from the corresponding reaction of trimethylhydroquinone dimethyl ether (2,5-dimethoxy-1,3,4-trimethylbenzene). The molecules of (IIa) and (IIb) each lie on a twofold axis passi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The majority of para-anisole derivatives have a CÐOÐCÐC angle close to planarity (< 15 or > 165 ), with a signi®cant difference in their OÐCÐC angles that can be attributed to steric and electronic effects. Two related examples have been reported by Wiedenfeld et al (2003).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…The majority of para-anisole derivatives have a CÐOÐCÐC angle close to planarity (< 15 or > 165 ), with a signi®cant difference in their OÐCÐC angles that can be attributed to steric and electronic effects. Two related examples have been reported by Wiedenfeld et al (2003).…”
mentioning
confidence: 89%
“…The MeO group at atom C14 displays an OÐCÐC distortion, with O3Ð C14ÐC13/C15 angles of 115.60 (13) and 123.34 (13) (transoid to atom C13 and the C 5 chain). These distortions, especially that of the C Me ÐOÐCÐC torsion-angle orientation with respect to the OÐCÐC angle, have been commented on previously (Bruno et al, 2001;Gallagher et al, 2001;Wiedenfeld et al, 2003).…”
mentioning
confidence: 99%
“…For the out-of-plane methoxy group, C6ÐO1ÐC7 and C3ÐO2ÐC9 are distinctly lower, at 114.7 (3) in (IIIa) and 113.6 (3) in (IIIb). We have previously found such effects in related compounds (Wiedenfeld et al, 2003(Wiedenfeld et al, , 2004. Such geometry is usual for compounds containing OCH 3 groups with different orientations about aromatic rings (Gallagher et al, 2001).…”
Section: Commentmentioning
confidence: 75%
“…Structures of compounds with 2,5-dimethoxy-3,4,6-trimethyl-substituted benzene rings are rare with only two entries (Wickramasinhage et al, 2016;Wiedenfeld et al, 2003) found in the CSD (Version 5.37, November 2015 with three updates; Groom et al 2016).…”
Section: Structure Descriptionmentioning
confidence: 99%